2020
DOI: 10.33225/jbse/20.19.234
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Volunteers’ Intention to Engage in Citizen Science: The Roles of Self-Efficacy, Satisfaction and Science Trust

Abstract: This research was carried out at the Science Volunteer Program 2018, which is run by Taiwan's Ministry of Science and Technology. The purpose of the research was to understand the effects of self-efficacy, satisfaction, and science trust on science volunteers' intention to continue volunteering. The research drew on the Social Cognitive Career Theory (SCCT) to test how social cognitive variables affect volunteers' intention to continue engaging in events and with organizations. A total of 156 volunteers taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…In other words, if students have high science self-efficacy, then they are expected to be more likely to engage with the community using their science skills . Our prediction is supported by the work of Kao et al. (2020) , who measured the effects of self-efficacy, satisfaction, and science trust on science volunteers’ intention to continue volunteering.…”
Section: Methods and Resultssupporting
confidence: 63%
“…In other words, if students have high science self-efficacy, then they are expected to be more likely to engage with the community using their science skills . Our prediction is supported by the work of Kao et al. (2020) , who measured the effects of self-efficacy, satisfaction, and science trust on science volunteers’ intention to continue volunteering.…”
Section: Methods and Resultssupporting
confidence: 63%
“…Morschheuser et al suggested that friendly cooperation and competition may significantly influence the crowdsourcing climate and individuals' self-evaluations, and then, affect participants' continued intentions [18]. The current paper established a research model based on Morschheuser's theoretical framework and applied high WSE and harmonious work climate as the predictors of continuance usage intention; following previous literature, reasonable task recommendation, effective cooperation, fair competition, and positive feedback were utilized as the antecedents of high WSE and harmonious work climate [18], [34], [35], [36], [41], [44]. Figure 1 depicts the research model and the hypothesized relationships proposed in this study.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Tu et al probed the role of hardiness in securities practitioners' web-based continuing learning; the research results revealed that WSE positively influences users' attitudes towards web-based continuing learning [33]. Kao et al investigated factors affecting volunteers' intention to engage in citizen science; they considered that WSE significantly influences individuals' satisfaction and sustained intentions [34]. Concerning the predictors of WSE in the context of online innovation, scholars considered that cooperation, competition, and feedback-related factors might affect the development of individuals' WSE.…”
Section: B Computer Self-efficacymentioning
confidence: 99%
“…Citizen science has gained its popularity in many different fields, for example, in biology, where people collect data on the movement and habitats of different species [14]; environmental studies, where citizens monitor water pollution [15]; education, where students acquire practical knowledge on science and technology [16]. Recently, citizen science has been noticed by policymakers and activists as a tool for enhancing participation of citizens in the public sphere [17,18].…”
Section: Role Of Citizens In Citizen Sciencementioning
confidence: 99%